PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN TERHADAP MOTIVASI BELAJAR SISWA - Haryana Rukmaningrum; Syamsuria; Basri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the influence of learning media on student learning motivation at SMP Negeri 3 Lappariaja. The background of this research is based on the importance of the role of learning media in creating an interesting, interactive, and learning process that is able to increase student learning motivation, especially in the current digital era. This study uses a quantitative approach with a survey method, and data collection is carried out through a questionnaire in the form of a Likert scale which is distributed to 26 respondents in grade VIII B.The results of data analysis using simple linear regression showed that learning media had a significant effect on student learning motivation, with a significance value of 0.000 and a regression coefficient of 0.738. The validity and reliability test of the research instrument showed that all questionnaire items were valid and reliable with a Cronbach's Alpha value of more than 0.9. These findings suggest that the use of appropriate learning media can increase students' enthusiasm, interest, and engagement in the learning process.